Too Soon to Say: International Criminal Law’s Role in the Conflict in Ukraine - Michelle Coleman (2022)
On 24 February 2022, Russia launched a widescale invasion of Ukraine resulting in an ongoing armed conflict. Since that date, numerous sources have been quick to call for the investigation and possible prosecution of international crimes arising out of the conflict. These calls to action open questions about whether international criminal law is an appropriate tool during armed conflict and what investigation and prosecution might be able to accomplish.